Multiple Determinations of Sperm DNA Fragmentation Show That Varicocelectomy Is Not Indicated for Infertile Patients with Subclinical Varicocele. (20th May 2014) - García-Peiró, Agustín; Ribas-Maynou, Jordi; Oliver-Bonet, María; Navarro, Joaquima; Checa, Miguel A.; Nikolaou, Alexandros; Amengual, María J.; Abad, Carlos; Benet, Jordi
Abstract : Varicocele is one of the most common causes of low semen quality, which is reflected in high percentages of sperm cells with fragmented DNA. While varicocelectomy is usually performed to ameliorate a patient's fertility, its impact on sperm DNA integrity in the case of subclinical varicocele is poorly documented. In this study, multiple DNA fragmentation analyses (TUNEL, SCD, and SCSA) were performed on semen samples from sixty infertile patients with varicocele (15 clinical varicoceles, 19 clinical varicoceles after surgical treatment, 16 subclinical varicoceles, and 10 subclinical varicoceles after surgical treatment). TUNEL, SCD, and SCSA assays all showed substantial sperm DNA fragmentation levels that were comparable between subclinical and clinical varicocele patients. Importantly, varicocelectomy did improve sperm quality in patients with clinical varicocele; however, this was not the case in patients with subclinical varicocele. In summary, although infertile patients with clinical and subclinical varicocele have similar sperm DNA quality, varicocelectomy should only be advised for patients with clinical varicocele.